Yoga for MS and related conditions [videorecording (DVD)] - Walters, Thomas, 1956-; Crotzer, Shoosh (Mobility Ltd., 1993)
Exercises designed for anyone with limited mobility including seniors, people with multiple sclerosis, arthritis or other limitations as well as people who are overweight or temporarily limited.